Imbalance in the Gut Microbiota of Children With Autism Spectrum Disorders - Ding, Hongfang; Yi, Xinhao; Zhang, Xiaohua; Wang, Hui; Liu, Hui; Mou, Wei-Wei (Frontiers in Cellular and Infection Microbiology, 2021)
Background: Autism spectrum disorder (ASD) is manifested as changes in children's complex behaviors, including social interactions and stereotypes. The purpose of this study was to assess the differences in gut microbiota (GM) between children with ASD and healthy controls. Methods: The study was performed on 25 children with ASD and 20 healthy children. Autistic symptoms were diagnosed and assessed with the Diagnostic and Statistical Manual for Mental Disorders (Fifth Edition (DSM-5)) and the Autism Treatment Evaluation Checklist (ATEC). Gastrointestinal (GI) symptoms were assessed with a GI Severity Index (GSI) questionnaire. The fecal bacteria composition was investigated by high‑throughput sequencing of the V3–V4 region of the 16S rRNA gene. The alpha diversity was estimated using the Chao, ACE and Shannon indexes. The unweighted UniFrac analysis and the PCA plots were used to represent the beta diversity. LEfSe and LDA were applied to assess the effect size of each differentially abundant taxon. Results: Children with high GSI scores had much higher ATEC Total scores than those with lower GSI-scores. GI symptoms were strongly correlated with the severity of autism symptoms. There was no difference of Chao, ACE and Shannon indexes between ASD patients and healthy controls. The PCA plots revealed a significant separate clustering in microbiota structure between two groups. Differences in the microbiota composition at the phyla, order, family, and genus levels between ASD and control groups were observed. There were significant differences in the overall relative abundances of Firmicutes and Actinobacteria between ASD patients and healthy controls. Dominant phyla of ASD were Firmicutes, Actinobacteria, and Bacteroidetes, followed by Proteobacteria. At the genus level, the dominant bacteria of ASD are mainly Faecalibacterium, Bacteroides, Prevotella_9, Blautia and Subdoligranulum. Conclusions: This study shows the relationship between the clinical manifestations of Autistic symptoms and GI symptoms. ASD patients have dysbiosis of gut microbiota, which may be related to the onset of ASD. These findings may be beneficial for developing ASD symptoms by changing gut microbiota.